Thin Capitalization Determinants in Manufacturing Companies In Indonesia - Sumarta, Nurmadi Harsa; Hananto, Septian Adi; Supriyono, Edy (Riset Akuntansi dan Keuangan Indonesia, 2021)
This study aims to analyze the determinants of thin capitalization practices on manufacturing companies in Indonesia. This study focuses on the manufacturing sector, which ranks the second largest recipient of foreign debt. The population of this study consisted of all manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. This study used the purposive sampling technique to determine samples. From that technique, 308 samples were obtained. The hypothesis analysis technique in this study employed the Ordinary Least Square (OLS) method. The results revealed that tax havens utilization and substantial foreign ownership positively affected the thin capitalization practice. Meanwhile, the presence of foreign directors in the company had a negative effect on the thin capitalization practice. This study could not prove the effect of multi-nationality on the thin capitalization practice.